2021
DOI: 10.1002/aur.2553
|View full text |Cite
|
Sign up to set email alerts
|

Social synchronization during joint attention in children with autism spectrum disorder

Abstract: Background: This study examined the social synchronization in children with autism spectrum disorder (ASD) when responding to others' joint attention. Social synchronization refers to an individuals' temporal coordination during social interactions, which has been found to play a crucial role in social development.De cient joint attention has been repeatedly found in individuals with autism spectrum disorder, and previous studies have demonstrated various explanations about it. In a more recent perspective, jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 73 publications
(136 reference statements)
0
16
0
Order By: Relevance
“…However, non-autistic participants were significantly more likely than autistic participants to return their visual attention to the social stimuli shortly afterward ( Del Bianco et al, 2021 ; Hedger and Chakrabarti, 2021 ). Further, autistic children shifted their gaze in response to the gaze of a social partner significantly more slowly that non-autistic children ( Liu et al, 2021 ). Longer latencies in gaze following are likely to reduce the extent to which relevant behavioural cues can be perceived and acted upon.…”
Section: Part 2 – Interpersonal Synchrony In Autismmentioning
confidence: 85%
See 1 more Smart Citation
“…However, non-autistic participants were significantly more likely than autistic participants to return their visual attention to the social stimuli shortly afterward ( Del Bianco et al, 2021 ; Hedger and Chakrabarti, 2021 ). Further, autistic children shifted their gaze in response to the gaze of a social partner significantly more slowly that non-autistic children ( Liu et al, 2021 ). Longer latencies in gaze following are likely to reduce the extent to which relevant behavioural cues can be perceived and acted upon.…”
Section: Part 2 – Interpersonal Synchrony In Autismmentioning
confidence: 85%
“…Converging evidence indicates that, on average, IS is reduced in autism ( McNaughton and Redcay, 2020 ). Studies employing structured experimental tasks involving pendulum swinging ( Fitzpatrick et al, 2016 ), chair rocking ( Marsh et al, 2013 ), movement improvisation ( Brezis et al, 2017 ) and gaze following ( Liu et al, 2021 ) all found lower levels of IS when one of the interacting partners was autistic, relative to when both partners were non-autistic. A similar pattern of results has emerged from the analysis of naturalistic interactions.…”
Section: Part 2 – Interpersonal Synchrony In Autismmentioning
confidence: 99%
“…Crucially though, the content of the activity could scaffold social attention itself. For instance, when engaged in a book sharing activity with their caregivers, ASD children devoted less visual attention to the other their TD peers, but this was attenuated when using a musical book rather than a picture book, suggesting musical activity to scaffold mutual engagement ( 56 ). Similarly, Glass and Yuill ( 60 ) found that the level of IMS varied across groups based on the task type.…”
Section: Resultsmentioning
confidence: 99%
“…Different ROIs have been selected by different groups: Liu et al. ( 56 ), as well as Glass and Yuill ( 60 ) selected 2 ROIs only (corresponding to each person) as being interested in a whole-body coordination, while other groups chose to differentiate between multiple ROIs within each individual [i.e., head and body in Georgescu et al. ( 86 ); head, hand, trunk in Noel et al.…”
Section: Resultsmentioning
confidence: 99%
“…Before the study, we confirmed that all of them had been diagnosed with HFA/ AS at Shanghai Pediatric Hospital or similar institutes in Shanghai. The same procedure we also used in our previous study (Liu et al, 2023). The children in the ASD group met the DSM‐5 diagnostic criteria.…”
Section: Methodsmentioning
confidence: 99%